Konserwatywna percepcja zmieniającej się rzeczywistości. Krytyczne spojrzenie na rozwój zawodowy dyrektorów szkół w Izraelu - Nets, Mali (Studia Edukacyjne, 2016)
As a part of the worldwide trend, in Israel the issues of accountability in management, the school improvement, and the learners’ achievements are topics on the public agenda. In the attempt to address these challenges, Israel implemented a reform in the professional development of the principals, which was applied to the system with the establishment of the School Leadership Institute, Avnei Rosha (2007). The theoretical model of the professional development is based on the career stages approach,1 which originated in the research studies on the career circles of teachers2 and principals. These models examined characteristics of different stages in the professional life track of the teacher3 as well as the mental aspect of the principals’ perception of management throughout the career.4 The Israeli model adopted these theories as the basis for the professional development of principals and formed a comprehensive program of learning from the stage of the entry into the role to the stage of the retirement.5 The article will propose a critical look at the professional development program of the school principals from the third year in the role and onwards, on the background of the new challenges with which the Israeli educational system copes. The article will focus on the theoretical and practical aspects of the question of the professional development of principals, will review the influences of recent reforms on the professional development of principals from the third y ear i n t he position, will p resent t he i mmanent g aps of t he I sraeli p rogram a pplied to t hese principals, and will suggest issues for future thought.